(untitled) (Annals of Medical Research, 2021)
Aim: It is to review the clinical features, and surgical, and visual outcomes of rhegmatogenous retinal detachment in a pediatric population.Material and Methods: Medical records of 31 children aged 16 years old or younger with rhegmatogenous retinal detachment were retrospectively analyzed. Cases of acute retinopathy of prematurity were excluded. The data for etiologies, risk factors, prior intraocular surgery, therapeutic approach options, anatomic and functional results were evaluated.Results: Thirty-three eyes of 31 patients with RRD were evaluated. The mean patient age was 11.42±3.82 years (range 3-16). There were 26 (83.9%) males and 5 (16.1%) females. The most common etiology was trauma. At presentation 57.5% of affected eyes (19/33) had a visual acuity worse than 20/400. Preoperative retinal tear was found in 60.6% (20/33) of patients. At initial examination, proliferative vitreoretinopathy was detected in 36.3% (12/33) of patients. The most common primary operation was scleral buckle with subretinal fluid drainage (69.6%, 23/33). Anatomical reattachment was accomplished in 84.8% of cases (28/33). At the final visit, 78.78% of affected eyes (26/33) had a better visual acuity when compared to preoperative examination. In nine of affected eyes (27.27%), visual acuity was 20/200 or better. Mean follow-up time was 37.5 months (range 3-72). Conclusion: In our series, pediatric RRD occurred most commonly in association with trauma. Most eyes were anatomically reattached, and most eyes retained vision of 20/800 or better. Preserving vision in children with RRD is of great importance because of high risk of vision threatening events to the fellow eye.